Impacts of pyrolysis temperatures on physicochemical and structural properties of green waste derived biochars for adsorption of potentially toxic elements - Muhammad, Nisar (2022)
This study comparatively investigated the influence of changes in pyrolysis temperature on the physicochemical, structural, and adsorptive properties of biochars derived from a green waste (Cynodon dactylon L.). For this purpose, the biophysically dried green wastes were pyrolyzed at 400 °C, 600 °C, and 800 °C under the same pyrolysis conditions. The results revealed that the physicochemical and structural properties were varied, depending upon the pyrolysis temperatures. With the increase of pyrolysis temperature, the surface functional groups were escaped, the structure became more porous (pore volume of 0.089 ± 0.001), the metal oxides were remained consistent, and the biochars turned into more alkaline nature (pH of 11.9 ± 0.2). Furthermore, as referring to the adsorptive performance for potentially toxic elements, with experimental adsorption capacity of up to 33.7 mg g-1 and removal rate up to 96% for a multi-metals containing solution, the biochars pyrolyzed at high temperature (800 °C) was significantly (p < 0.05) higher than those pyrolyzed at low temperature (400 °C). According to the physicochemical and structural properties, and the adsorptive performances of the biochars, the optimal pyrolysis temperature was herein recommended to be 800 °C.